GEOCHEMISTRY, PETROGENESIS AND TECTONO-MAGMATIC SIGNIFICANCE OF VOLCANIC AND SUBVOLCANIC ROCKS FROM THE KOZIAKAS MÉLANGE (WESTERN THESSALY, GREECE) - Saccani, Emilio; Photiades, Adonis; Padoa, Elisa (Ofioliti, 2003)
The Koziakas ophiolites have previously been interpreted as a Jurassic complex generated at a mid-ocean spreading ridge, and have been subdivided into a lower volcanic unit and an upper ultramafic unit.The data presented in this paper demonstrate that the lower volcanic unit is, in fact, a tectonic mélange consisting of a polygenetic, multiple packet of stacked thrust-bound slices, representing distinct volcanic sequences and radiolarian chert successions.Volcanic sequences include pillowed and massive lava varieties, which are frequently crosscut by dikes of various nature, including boninitic dikes. Both lava varieties and dikes are predominantly aphyric, though a few samples display slightly porphyritic textures, where phenocryst assemblages include olivine and/or plagioclase in pillow and massive lavas, clinopyroxene, plagioclase and sanidine in trachytic dikes, clinopyroxene in boninitic dikes.Geochemical data point out the presence of three compositionally distinct groups of lavas: (1) transitional to alkaline basalts, trachyandesites, trachytes; (2) tholeiitic basalts; (3) very low-Ti (boninitic) basaltic andesites and andesites. The transitional to alkaline rocks displays high Nb/Y ratios and enriched incompatible element characteristics, similar to those of many intraplate oceanic island basalts (OIB).The tholeiitic group display lower abundances of incompatible elements and includes rocks resembling normal mid-ocean ridge basalts (N-MORB) with light REE (LREE) depletion (LaN/SmN = 0.29) and very low Ce/Y, Ta/Hf, Th/Yb ratios, as well as rocks resembling enriched mid-ocean ridge basalts (EMORB) showing moderate LREE enrichment (LaN/SmN = 1.26-1.52) and Ce/Y, Ta/Hf, Th/Yb ratios higher than those of N-MORBs. The very low-Ti group displays greatly depleted incompatible element abundances and the U-shaped REE patterns typical of boninites generated in suprasubduction settings.The Koziakas Mélange appears to have formed due to tectonic dismemberment and accretion of material generated in an oceanic environment (MORBs and OIB-type rocks), possibly in an intra-oceanic forearc setting. After their accretion these rocks were affected by widespread boninitic dikes generated by partial melting of depleted peridotites in the fore-arc setting.The record of different lava types in the Koziakas Mélange is in accordance with the general geological evolution of the Neo-Tethyan Pindos oceanic basin, from the Permo-Triassic rifting to the Middle-Late Jurassic intra-oceanic convergence phase.